Determination of Zero Rupiah Rate Against Non-Tax State Revenue for Intellectual Property Rights Services - Nevey Varida Ariani; Amirudin Amirudin (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The government continues to encourage the public to innovate to grow intellectual property by providing protection and legal certainty, including the application of Non-Tax State Revenue (Penerimaan Negara Bukan Pajak - PNBP) of Zero Rupiah. The problem is how to set a zero IDR Rupiah rate on non-tax state revenues for intellectual property services. The research method used is normative juridical. Provision of a non-tax state revenue rate of zero rupiahs determined based on certain conditions for intellectual property services such as social, religious, and state activities, and given specifically to underprivileged communities, students or /college students, Micro, Small and Medium Enterprises, or force majeure conditions, as well as activities that support the programs of the Ministry of Law and Human Rights, especially the Directorate General of Intellectual Property. Optimization of the budget or the achievement of PNBP in the Directorate of Intellectual Participation needs to be monitored and evaluated every year. Therefore, it is necessary to have a legal basis in the form of a Regulation of the Minister of Law and Human Rights concerning the Amount, Requirements, and Procedures for the imposition of Non-Zero Rupiah State Revenue Rates for Intellectual Property Services by first through the approval of the Minister of Finance